CONCENTRATION LEVELS OF PHYSICO-CHEMICAL PROFILES AND QUALITY ASSESSMENT OF GROUNDWATER: A CASE STUDY OF SOUTHERN IJAW, BAYELSA STATE, SOUTHERN NIGERIA - Nwankwoala, H.O; Peterside, A.N; Hart, A.I (Engineering Heritage Journal)
This study examined the concentration levels of physico-chemical profiles of groundwater quality of communities in Southern Ijaw Local Government Area of Bayelsa State, Nigeria. The seasonal variation of groundwater quality were evaluated. Fifteen (15) communities within the LGA were selected and groundwater from hand-dug well (HDW-15samples) and borehole (BH-15samples) was sourced during the wet season (July) and dry season (March) and analyzed for seasonal variations. The difference in the mean of the parameters investigated during the dry and wet season revealed the difference in concentration level as influenced by the season attributes. The HDW showed a very strong correlation in wet and dry season physicochemical properties as well as no significant difference in the physicochemical properties of groundwater at both seasons. Also, the results of borehole water sample showed a very strong correlation in wet and dry season physic-chemical properties with no significant difference in the physicochemical properties of water at both seasons. There are similarities in various natural and anthropogenic activities influencing the concentrations during both wet and dry seasons. The mean values of parameters such as pH, TDS, TSS, Bicarbonate, Cl, SO34, NO2, Ca, Mg, K and P are within the permissible limit of WHO and NSDWQ during both seasons except TC.